2010
DOI: 10.1007/s00404-010-1787-4
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in pregnant women

Abstract: Our study shows the high prevalence of HPV infection in pregnant women in Lithuania. The majority of pregnant women's HPV infection was cleared during the pregnancy. Only in a few cases a new HPV infection was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
1
20
1
1
Order By: Relevance
“…Similarly, we have demonstrated that the risk for incident oral HPV infections and their persistence is markedly decreased by a new pregnancy [15,27]. Most previous studies have focused only on differences in HPV prevalence among the pregnancy trimesters [28,29]. A recent study showed that among persistent HPV infections, childbirth proved to be a cofactor for high-grade cervical disease but not pregnancy [30].…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, we have demonstrated that the risk for incident oral HPV infections and their persistence is markedly decreased by a new pregnancy [15,27]. Most previous studies have focused only on differences in HPV prevalence among the pregnancy trimesters [28,29]. A recent study showed that among persistent HPV infections, childbirth proved to be a cofactor for high-grade cervical disease but not pregnancy [30].…”
Section: Discussionmentioning
confidence: 65%
“…However, not all studies have confirmed an increased risk of HPV infection in pregnancy, and yet other reports have suggested that the clearance of HPV infection is not different between pregnant and non‐pregnant patients . As such, the association between HPV infection and pregnancy remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, not all studies have confirmed an increased risk of HPV infection in pregnancy, 9,18 and yet other reports have suggested that the clearance of HPV infection is not different between pregnant and non-pregnant patients. 10,19 As such, the association between HPV infection and pregnancy remains controversial. We propose that this apparent contradiction in the literature may be due in part to the fact that HPV prevalence rates change throughout gestation, a fact that is not accounted for in these prior publications.…”
Section: Discussionmentioning
confidence: 99%
“…Domza et al [8] determined the prevalence, serotype and the change of prevalence of HPV during pregnancy by taking cervicovaginal washings from 213 women before pregnancy (baseline) and again in the first and third trimester. At the time of the first sample, 17.8% of women (38/213) were HPV positive, and of these 38, 20 (52.6%) had HR-HPV serotypes.…”
Section: Hpv In Pregnant and Non-pregnant Womenmentioning
confidence: 99%